1997
DOI: 10.1046/j.1471-4159.1997.69020639.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of [3H]Phosphatidylinositol and [3H]Phosphatidylinositol 4,5‐Bisphosphate Hydrolysis in Postmortem Human Brain Membranes and Characterization of Stimulation by Dopamine D1 Receptors

Abstract: Assessing the function of the phosphoinositide signal transduction system in membranes prepared from postmortem human brain by measuring the hydrolysis of exogenous labeled phosphoinositides has been applied to studies of a variety of CNS disorders in recent years. Two issues concerning such studies were addressed in the current investigation: how do [3H]phosphatidylinositol and [3H]phosphatidylinositol 4,5‐bisphosphate compare as substrates, and how do dopamine D1 receptors influence phosphoinositide signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 15 publications
2
33
2
Order By: Relevance
“…11). One possibility is that dopamine acts on a putative PLC-linked D1 class DAR (9,10,60). Indeed, SKF83959, a specific agonist for this putative PLC-linked D1 class DAR (11), induced Ca 2ϩ release from intracellular stores in MSN (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…11). One possibility is that dopamine acts on a putative PLC-linked D1 class DAR (9,10,60). Indeed, SKF83959, a specific agonist for this putative PLC-linked D1 class DAR (11), induced Ca 2ϩ release from intracellular stores in MSN (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Although a number of studies have found that G ␣q couples the dopamine receptor to PLC (Felder et al, 1989;Undie and Friedman, 1990;Pacheco and Jope, 1997), the recent identification of a selective agonist, SKF83959 (Panchalingam and Undie, 2001;Jin et al, 2003), for this pathway has allowed the detailed investigation of signal transduction and function of this dopamine receptor. The present data demonstrate that activation of the PI-linked D 1 dopamine receptor differentially regulates the cdk5 and CaMK II pathways.…”
Section: Discussionmentioning
confidence: 99%
“…activation of phospholipase C␤ (PLC␤), which hydrolyzes phosphatidylinositol (PI) into diacylglycerol and inositol trisphosphate (IP 3 ) (Felder et al, 1989;Undie and Friedman, 1990;Pacheco and Jope, 1997). IP 3 is an important second messenger that elicits the release of calcium from intracellular stores.…”
mentioning
confidence: 99%
“…These results strongly support the idea that the enhancement of dopamine-induced Ca 2+ responses after exposure to BPA could lead to an increase in the excitability of the central dopaminergic neurons. It has been reported that stimulation of dopamine D1 receptor increases intracellular Ca 2+ concentration via activation of phospholipase C-inositol-1,4,5-trisphosphate signaling pathway (Pacheco and Jope, 1997;Jin et al, 2003). Dopamine-induced Ca 2+ responses are also modulated by dopamine D2 receptor (Zhu et al, 1997;Takeuchi et al, 2002).…”
Section: Activation Of Astrocytes By Bpamentioning
confidence: 99%